Distancing from the Present: Nostalgia and Leisure in Lockdown. (3rd March 2021) - Gammon, Sean; Ramshaw, Gregory
Abstract: This paper considers the role of nostalgia-based leisure in the present COVID-19 pandemic. Enforced lockdowns and social distancing initiatives have been met with various media channels replaying famous sport matches, classic films and memorable concerts from the past. Furthermore, social media is full of families interacting more; playing traditional board games and numerous other leisure-related activities such as baking bread and making fresh pasta. Nostalgia may well end up being one of the primary coping mechanisms (for all generations) of enduring isolation, fear - and a general loss of freedom. It is also worth considering whether we are now creating our own future nostalgia where, when the crisis is through, we will long for the social bonds and sense of community the pandemic created.